2022
DOI: 10.3390/jcm11030857
|View full text |Cite
|
Sign up to set email alerts
|

Do the Current Guidelines for Heart Failure Diagnosis and Treatment Fit with Clinical Complexity?

Abstract: Heart failure (HF) is a clinical syndrome defined by specific symptoms and signs due to structural and/or functional heart abnormalities, which lead to inadequate cardiac output and/or increased intraventricular filling pressure. Importantly, HF becomes progressively a multisystemic disease. However, in August 2021, the European Society of Cardiology published the new Guidelines for the diagnosis and treatment of acute and chronic HF, according to which the left ventricular ejection fraction (LVEF) continues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 110 publications
1
29
0
Order By: Relevance
“…Many targets have been achieved and many more are still to be pursued regarding the virtual follow up of HF patients: (i) the possibility of following up with all patients discharged after a hospitalization, according with the times suggested by the Guidelines [ 1 ] and major clinical trials, in order to prevent disease exacerbation and HF progression; (ii) the possibility of stratifying HF patients, identifying patients at short-term risk of disease exacerbation who can benefit from a long-term virtual follow up and reserving in-person visits for high-risk patients; (iii) the possibility of titrating therapy quickly, as suggested by the Guidelines [ 1 ], and improving treatment adherence [ 42 ]; (iv) the possibility of prescribing further exams to complete a diagnostic path; (v) the possibility of relieving the congestion of hospital HF outpatients’ services, reducing waiting time. These aspects may bring benefits in terms of patients’ care, hospital organization, and healthcare costs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many targets have been achieved and many more are still to be pursued regarding the virtual follow up of HF patients: (i) the possibility of following up with all patients discharged after a hospitalization, according with the times suggested by the Guidelines [ 1 ] and major clinical trials, in order to prevent disease exacerbation and HF progression; (ii) the possibility of stratifying HF patients, identifying patients at short-term risk of disease exacerbation who can benefit from a long-term virtual follow up and reserving in-person visits for high-risk patients; (iii) the possibility of titrating therapy quickly, as suggested by the Guidelines [ 1 ], and improving treatment adherence [ 42 ]; (iv) the possibility of prescribing further exams to complete a diagnostic path; (v) the possibility of relieving the congestion of hospital HF outpatients’ services, reducing waiting time. These aspects may bring benefits in terms of patients’ care, hospital organization, and healthcare costs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…HF is a clinical multisystemic syndrome defined by specific symptoms and signs due to structural and/or functional heart abnormalities, which lead to inadequate cardiac output and/or increased intraventricular filling pressure [ 31 ]. In this study, we aimed to assess the prevalence of HF and its subtypes in a Portuguese center, as well as associated risk factors, such as T2D.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by a potential improvement in LVEF over time in the group with a lower baseline LVEF, which could be associated with improvements in HRQoL. However, it could also reflect the several pitfalls that the actual classification of HF based on LVEF values has [ 35 ]. Moreover, in our study, a trend towards a lower proportion of all-cause hospitalization was found in the group with HRQoL improvement.…”
Section: Discussionmentioning
confidence: 99%